Escaping the unemployment trap: The case of East Germany - Christian Merkl; Dennis J. Snower (Kiel Institute for the World Economy (IfW), 2007)
This paper addresses the question of why prolonged regional unemployment differentials tend to persist even after their proximate causes have been reversed (e.g., after wages in the highunemployment regions have fallen relative to those in the low-unemployment regions). We suggest that the longer people are unemployed, the greater is the likelihood of falling into a low-productivity "trap", through the attrition of skills and work habits. We develop and calibrate a model along these lines for East Germany and examine the effectiveness of three employment policies in this context: (i) a weakening of workers' position in wage negotiations due to a drop in the replacement rate or firing costs, leading to a fall in wages, (ii) hiring subsidies, and (iii) training subsidies. We show that the employment effects of these policies depend crucially on whether low-productivity traps are present.
More recent version: http://hdl.handle.net/10419/24858
Keywords: J64; J31; E24; J30; 330; labor market traps; calibration; East Germany; labor markets; Langzeitarbeitslosigkeit; Arbeitsproduktivität; Qualifikation; Arbeitsmarktpolitik; Kündigungsschutz; Reform; Lohnsubvention; Berufsbildungspolitik; Wirtschaftspolitische Wirkungsanalyse; Schätzung; Neue Bundesländer